The Effect Of Profitability And Leverage On Corporate Social Responsibility Disclosure: Study of the Annual Report of BUMN operating in the insurance sector for the 2016-2019 period - Hanifah, Azimah (International Journal of Advanced Multidisciplinary, 2023)
The aim of this research is to determine and analyze: (1) Profitability (2) Leverage; (3) Disclosure of Corporate Social Responsibility; and (4) The influence of profitability and leverage on disclosure of corporate social responsibility in the annual reports of state-owned companies operating in the insurance and financial services sector for the 2016-2019 period, both simultaneously and partially. The research method used in this research is a time series, the unit of analysis in this research is the Annual Report of a BUMN Company operating in the Insurance and Financial Services Sector for the 2016-2019 Period. The type of investigation is causality, and the time horizon in this research is cross-sectional. Based on the research results, it was found that the profitability of state-owned companies operating in the insurance and financial services sector for the 2016-2019 period was good, the leverage of state-owned companies operating in the insurance and financial services sector for the 2016-2019 period could generally be said to be good, the disclosure of corporate social responsibility in State-owned companies operating in the insurance and financial services sector for the 2016-2019 period are currently considered good. Profitability and Leverage influence the Disclosure of Corporate Social Responsibility in the Annual Reports of BUMN Companies operating in the Insurance and Financial Services Sector for the 2016-2019 Period simultaneously and partially. However, partially Profitability is more dominant in influencing Corporate Social Responsibility Disclosure than Leverage Because profitability is more dominant in influencing Corporate Social Responsibility Disclosure, it is the first priority in increasing Corporate Social Responsibility Disclosure. Therefore, state-owned companies operating in the insurance and financial services sector are advised to consistently maintain existing profitability, so that the company's performance continues to increase.